Urdu Ka Guldasta (Khususi Isha'at) Sooraj mukhi (class 7) - Fouzia ahsan farooqui (Oxford University Press; Pakistan, 2022)
Sooraj Mukhi Class 7 is an educational resource designed to engage students with a variety of lessons and activities that enhance their understanding of key subjects at the seventh-grade level.